THE IMPACT OF PERCEIVED TRANSPARENCY, PERCEIVED FAIRNESS, DAN PERCEIVED CONTROLLABILITY OF COMPENSATION SYSTEM TO EMPLOYEE’S MOTIVATION IN PT ANTAM PERSERO, TBK UNIT GEOMIN – PULOGADUNG - Shandy Puspita (Jurnal Bina Manajemen, 2018)
The purposed of this research is to finding and analyzing whether the variables of perceived transparency, perceived fairness, and perceived controllability, which are scales to measure the effectiveness from compensation system, have a relationship and positive impact to extrinsic and intrinsic motivation. The research conducted in one of unit PT Aneka Tambang,Tbk called Geomin. Research methods which conducted in this research are descriptive and quantitative approaches. Data collection techniques which used is primary data where collected by questionnaires whose probability sampling is judgmental. Data analysis techniques used simple linear regression analysis with SPSS version 19. The finding of this research are variables of Perceived Transparency and Perceived Controllability have a positive relationship with Extrinsic Motivation, but variable of Perceived Fairness has no relationship with Extrinsic Motivation. Variables of Perceived Transparency, Perceived Fairness, and Perceived Controllability altogether have a relationship with Intrinsic Motivation, but not significant.